Analisis Pengaruh Leverage dan Profitabilitas Terhadap Struktur Modal Perusahaan Manufaktur Syariah di Indonesia - Aulia Septa; Wahyu Putra; Niken Aristania; Dwi Ermayanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study analyses the impact of leverage and profitability on the capital structure of Indonesian Sharia manufacturing companies listed in the Jakarta Islamic Index (JII) during the period of 2019-2021. The type of research used is quantitative. The problem of this research is the suboptimality in determining the capital structure, which leads to financial difficulties for the company. The research was conducted in Indonesia involving 16 sharia manufacturing companies as respondents. The analysis method used is multiple linear regression with the assistance of SPSS version 25 to test the effect of leverage and profitability on capital structure. The research results indicate that simultaneously, the calculated F value is 64.098 with a significance value of 0.000, which is less than 0.050. This shows that leverage and profitability have a significant effect on capital structure. However, in the partial analysis, it was found that only leverage has a positive and significant effect on capital structure, with a β1 value of 0.211, which is positive, and a significance value of 0.032 (< 0.05). Meanwhile, the profitability variable shows a negative and significant result on capital structure, with a β2 value of -0.516, which is negative, and a significance value of 0.018, which is less than 0.05. This research suggests that companies should consider the balance between the use of debt and equity in achieving an optimal capital structure, thereby enhancing the value and performance of the company.